VD_FINDINFO HC / 2013 / 343 vom 21. Mai 2013 - VD Tribunal cantonal (2013)
CONDITION DE RECEVABILITÉ, VICE DE FORME, RECTIFICATIONEN GÉNÉRAL | 132 CPC (CH), 334 CPC (CH), 59 al. 2 let. c CPC (CH), 60 CPC (CH)